Ta’tsīru Wasīlat al-Mutāqāṭi‘ah bil-Lughah al- ‘Arabiyyah lii Fahmi Qawā‘id ‘Ilmi an-Naḥwi Ladāy Tullāb - Muhammad Zulfikar Al-umar Khan; Muhammad Syaifullah; Jauharotun Nafisah (CV. Creative Tugu Pena, 2025)
This study aims to examine the effect of using Arabic crossword puzzle media in improving students’ understanding of Arabic grammar (nahwu) rules at Darul Ma’arif Islamic Boarding School, East Lampung. The background of this research is based on the importance of education as a key factor in societal progress, as well as the significance of the Arabic language—particularly grammar (nahwu)—in understanding Islamic texts. However, the teaching of nahwu is still largely dominated by traditional methods such as lectures and memorization, which often result in low student participation and difficulties in applying grammatical rules in practice. The objective of this study is to measure the effectiveness of crossword puzzle media as an interactive learning tool in enhancing students’ understanding of grammar rules, focusing on Jurumiyah-level students. The study employs a quantitative experimental method using a pretest-posttest design. Data collection techniques include tests, questionnaires, observations, interviews, and documentation. The results show a significant improvement in students’ understanding, with the mean score increasing from 69.50 in the pretest to 85.50 in the posttest, with a statistically significant difference (Sig. = 0.000 < 0.05). In addition, the crossword puzzle media proved effective in increasing students’ learning motivation, enhancing participation, and developing critical thinking and classroom interaction skills. In conclusion, the use of crossword puzzle media is an effective method in teaching Arabic grammar, particularly in Islamic boarding school environments, as it combines educational and entertaining elements. This study contributes academically to the development of Arabic language teaching methods through educational game-based learning. It also recommends broader use of interactive learning media and suggests further research with larger samples and different educational levels to obtain more comprehensive results.